BS EN ISO/IEC 20243-2. Information technology. Open Trusted Technology ProviderTM Standard (O-TTPS). Mitigating maliciously tainted and counterfeit products. Part 2. Assessment procedures for the O-TTPS (4th April 2023) - British Standards Institution,
No abstract available